The transition to renewable energy and its role in achieving sustainable development in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aims to study the reality of both conventional and renewable energy in Syria, before and after the war, and to study the necessity of switching to renewable energy sources to achieve sustainable development in its three dimensions (economic, social, and environmental). The research referred to the policies and projects that were established and approved in the field of renewable energy. In Syria, the research relied on the descriptive analytical approach, and the study concluded that the depletion of traditional energy sources, the war on Syria and its devastating results, and the departure of a large number of power and oil stations from service, led to the need to go to more renewable energy sources, and that investment in the field of renewable energy contributes In achieving the seventh goal of the sustainable development goals in Syria with its three dimensions (economic, social and environmental).